2016
DOI: 10.2174/1874210601610010538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LED and Argon Laser on Degree of Conversion and Temperature Rise of Hybrid and Low Shrinkage Composite Resins

Abstract: Objectives:Different light curing units are used for polymerization of composite resins. The aim of this study was to evaluate the degree of conversion (DC) and temperature rise in hybrid and low shrinkage composite resins cured by LED and Argon Laser curing lights.Materials and Methods:DC was measured using FTIR spectroscopy. For measuring temperature rise, composite resin samples were placed in Teflon molds and cured from the top. The thermocouple under samples recorded the temperature rise. After initial ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…38 Calura et al underlined the shortest irradiation time of lasers when compared to halogen lamps 39 while Shanthala and Munshi, in an in vitro study on primary teeth, showed with a 10-second laser exposure, a shear bond strength higher than the one obtained with a halogen lamp polymerization with a 40-second exposure, 40 and these data were also confirmed by the study of Fleming and Maillet. 41 Pahlevan et al 42 measured the degree of conversion (DC) using Fourier-transform infrared spectroscopy and showed that the argon laser gave the lowest temperature rise, even if the DC obtained by the different curing units was not significantly different.…”
Section: Composite Resin Photopolymerizationmentioning
confidence: 99%
“…38 Calura et al underlined the shortest irradiation time of lasers when compared to halogen lamps 39 while Shanthala and Munshi, in an in vitro study on primary teeth, showed with a 10-second laser exposure, a shear bond strength higher than the one obtained with a halogen lamp polymerization with a 40-second exposure, 40 and these data were also confirmed by the study of Fleming and Maillet. 41 Pahlevan et al 42 measured the degree of conversion (DC) using Fourier-transform infrared spectroscopy and showed that the argon laser gave the lowest temperature rise, even if the DC obtained by the different curing units was not significantly different.…”
Section: Composite Resin Photopolymerizationmentioning
confidence: 99%
“…Quartz-tungsten-halogen (QTH) LCUs have been the established gold standard for this purpose. However, following the advent of light-emitting diode (LED) LCUs, which have multiple benefits, QTH LCUs have been largely replaced with LEDs [ 2 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Case Reports in Dentistry Due to the polymerization shrinkage which is the main drawback of direct composite restorations, dentists may encounter many problems in selecting these restorations [13]. However, Stress Reduced Direct Composite (SRDC) technique could be considered as an alternative to indirect restorations [8].…”
mentioning
confidence: 99%